Atomic scale epitaxial growth of BaTiO3 thin films by laser molecular beam epitaxy - 王会生 马昆 刘彦巍 彭志强 崔大复 吕惠宾 周岳亮 陈正豪 李林 杨国桢 (Science China. Mathematics, 1997)
By using laser molecular beam epitaxy (L-MBE), atomic scale epitaxial growth of BaTiO3(BTO) thin films on SrTiO3 (STO) substrates is achieved. Measurements of reflection high energy electron diffraction (RHEED), X-ray diffraction (XRD), scanning electron microscopy, and transmission electron microscopy reveal that the BTO films are c-axis oriented single crystals with smooth surface. The multi-layer ferroelectric/superconducting heterostructures are also prepared and the ferroelectric properties of BTO films are studied. The results show that by using L-MBE technique, high quality BTO films and improved device performance can be obtained.